The presumption of death: a comparative appraisal from the perspective of the common law, Malaysian law and shariah - Shair Mohamad, Mohd Akram; Ramlee Saad, Zulfakar (Serials Publications, 2015)
Section 108 of the Evidence Act 1950 states ‘When the question is whether a man is alive or dead, and it is proved that he has not been heard of for seven years by those who would naturally have heard of him if he had been alive, the burden of proving that he is alive is shifted to the person who affirms it.’ This section reflects the English common law. In other words, if a person has not been heard of for at least seven years both the Evidence Act 1950 and the common law create a rebuttable presumption of law that, that person is dead, and the burden of proving that he is alive is shifted to the other side. However, the exact date of death after the expiry of seven years period is not a matter of inference but a matter of evidence. Under the common law, there are two views as to the date on which the fact of the death may be presumed. The stricter view says that the fact of death may be presumed retrospectively, while the laxer view suggests that the fact of death may be presumed prospectively. Unlike the English common law which accommodate both views but prefers the laxer view, so far the Malaysian and Indian courts followed the stricter view. Shariah law too recognises the concept of presumption of death but wisely it is not stuck with the common law and Evidence Act notion of not less than seven years. Interestingly, it has followed the earlier view of four years period. However, it shares the common law view that there is no presumption as to the exact date of the fact of death.